O corpo no Hatha-yoga-ocidentalizado:um mundo de concepções - Romão, Ricardo Soares (2019)
The body represents important transformations of human life and culture. This study seeks to understand the conceptions of body for hatha-yoga instructors in the city of João Pessoa-PB through a qualitative approach, with the participation of 15 instructors of Paraíba’s Yoga Association. The instrument used in data collection was the semi-structured interview, whose data were analyzed based on the Bardin Content Analysis. It is observed that in the classes of hatha-yoga there are characteristics for a body practice oriented to the physical conditioning, which influence the classes, although they are not present in the corporal conception of the instructors. These instructors exhibit difficulties to integrate the knowledge of the tradition with the class methodology, but they build a necessary bridge to a genuine experience of interiority and self-knowledge, based on hatha-yoga’s conception of body. It is possible to conclude that the participating instructors have bodily conceptions that constitute a psychosomatic experience in a physical, emotional, psychological and spiritual sense.